Validity of MABESTA: A 3D Visualization-Based Interactive Learning Media for Junior High School Students - Mochammad Ricky Rifa'i; Wachju Subchan; Trapsilo Prihandono (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2026)
The development of information and communication technology encourages educational innovation, especially science learning in junior high schools which is still dominated by lecture methods and conventional media, which causes low student activity and learning outcomes in the material of the earth and the solar system. Interactive learning media